Judicial Amnesty And Its Effect On Disciplinary Responsibility To The Public Servant - Peshawa Khidher Rasul; Shwan Omer khudhur; Viyan Hassan Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Judicial amnesty is one of the main issues that raises many inquiries, The most important of which is the problematic of the extent of the impact of the judicial amnesty on the accused employee on his disciplinary accountability for the act he committed and which resulted in both criminal and disciplinary responsibilities, On the basis of this problem, we discussed the topic (judicial amnesty and its impact on the disciplinary responsibility of the public employee) according to the analytical approach and comparison between laws that contain different legal provisions, In order to analyze the legislative texts in Iraq and other countries that adopt a system of judicial amnesty and compare them with some, in order to find the right direction regarding it. Through our study we found that, judicial amnesty generally haven’t effect on the disciplinary responsibility of a judicially pardoned employee, and when referring to the Iraqi State Employee Discipline Law No. (14) Of 1991 amended, We find that the administration has the right to discipline the employee, despite his judicial exemption, but by referring to the text of Article (8 / VII / A, B) and Article (8 / VIII / B) of the aforementioned law, we find that the administration cannot impose the punishment of dismissal and removal except If a court ruling is found, the employee will be convicted, This means that the administration must impose other penalties stipulated in Article (8) mentioned above, in a manner consistent with the gravity of the act committed by the employee who is judicially pardoned. In the context of seeking to solve these problems, the legislator recommended that we need to amend Article (129 / A) of the Iraqi Criminal Procedure Law No. (23) For 1971 amended, and Article (8 / VIII / A) of the Iraqi State Employee Discipline Law No (14) for 1991 amended.